INCIDENT MANAGEMENT IN ITSM USING ARTIFICIAL INTELLIGENCE - A. V. Blinnikova; Ju. O. Nesterova (Вестник университета)
Due to the development of the digital economy and the increasing importance of information technologies in modern companies, there is a need to ensure the required level of quality of information technology services provided. At the same time, one of the most important processes for achieving effective work of employees and technologies is incident management. The business user must have continuous access to the necessary resources of the information system, and the decision in the event of an incident should not be delayed indefinitely, suspending the business process in the company. Approaches to optimizing the incident management structure based on artificial intelligence tools, including machine learning, have been considered in the article. The positive aspects of using the artificial intelligence in incident management, real examples of companies and projects have been designated, and also the modern process of user support from detecting an incident until solving it has been analysed and presented.